The relevance of post‐traumatic stress disorder as a moderator of the relationship between experience of violent or sexual assault and opioid use in adulthood. (9th November 2021) - Wojciechowski, Thomas
Abstract: Background: Past research has indicated that individuals suffering from post‐traumatic stress disorder (PTSD) may demonstrate increased sensitivity to stress exposure following onset of the disorder. Thus, having PTSD may amplify the effects of subsequent stressors. This has been found to be relevant in some forms of substance use but relationships between PTSD, new stress and opioid use specifically has not been examined. Aims: To explore interactions between PTSD, new victimisation and opioid use and test the hypothesis that PTSD will moderate any victimisation–opioid use relationship. Methods: The pathways to desistance data were used in analyses. A series of logistic regression models were used to test both direct effects of victimisation and PTSD on opioid use and interactions between them. Results: The sample was comprised of a male majority (male N  = 1, 170; female N  = 184). Results indicated that neither PTSD nor victimisation were significant predictors of opioid use. PTSD was found to moderate the relationship between victimisation and opioid use in the hypothesised manner. Conclusions: There may be clinical implications of these results relating to both inpatient and outpatient treatment. Regular trauma screening, additional victims' services and trauma‐informed care may help to reduce the risk of opioid use among individuals suffering from PTSD.